Lindo balão azul: música e astronomia nos anos iniciais do ensino fundamental - Rugene, Rosilene Braga (Universidade Federal de São Carlos, 2022)
The present research was based on the importance of working Astronomy in Art classes for students in the early years of elementary school, in an interdisciplinary proposal to use the language of Art, music, as a motivating element for the acquisition of astronomical knowledge. The present study aims to develop a didactic sequence that enables the learning of astronomical content, from an educational practice that allows a union between Art and Astronomy. The work was developed with students enrolled in the early years of elementary school, in the city of Rio Claro - SP, with the suggestion of producing a pedagogical proposal explored in art classes. The purpose of promoting the acquisition of astronomical concepts from the analysis of the lyrics of a Brazilian popular song, has the intention of a more attractive and significant teaching proposal for the students, verifying if they materialize the idea and the concept that was transmitted. The methodology employed in this research is classified as qualitative in nature, with an experimental research design, without a control group. Through discussions in the classroom, with the use of the records, a satisfactory result of the research was evidenced, and it became evident that several participants of the research acquired and broadened their knowledge of astronomy through the research intervention.
Beautiful blue balloon: music and astronomy in the early years of elementary education
Keywords: Astronomia; Arte; Música; Educação; Interdisciplinaridade; Astronomy; Art; Music; Education; Interdisciplinarity; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM